Tidal Data Analysis Based on Season Using Admiralty Method in Lasolo Bay Waters, Southeast Sulawesi - Rachmawati Rachmawati; Irawati Irawati; Syamsul Razak Haraty (Jurnal Perikanan dan Kelautan, 2024)
Research on tidal analysis based on seasons has been carried out in Lasolo Bay, Southeast Sulawesi, using secondary data, namely tidal data in 2021 in January representing the western season, April representing the transition season I, July representing the eastern season and October representing the transition season II. This study aims to determine the type of tides formed and the value of sea level elevation in each season at the research site. Tidal data processing uses the admiralty method, producing amplitudes and phase differences from 9 main harmonic components. The analysis results of the calculation of formzhal numbers show that the type of tides formed in Lasolo Bay is a mixed type of double daily inclined with a formzhal number value of 0.5618-0.7059. In addition, based on the calculation of sea level elevation, the maximum average sea level (MSL) occurs in the second transition season (October), which is 532 cm, and the western season (January) is 460 cm. For the other two seasons, the first transitional season (April) and the eastern season (July) have an average sea level of 101 cm and 130 cm.